Improving overall thermal transfer value of office tower building in Malaysia, case study : Ministry of Women Family and Community Development, Lot 4G11, Putrajaya / Azman Zainonabidin and Amirul Amin Ismail - Azman, Zainonabidin; Amirul Amin, Ismail (2015)
This paper presents the Overall Thermal Transfer Value (OTTV) and the energy consumption of air-conditioned office building in Malaysia. The study have been conducted to investigate the OTTV of Ministry of Women Family and Community Development’s office block at Lot 4G11, Putrajaya. OTTV calculation, energy consumption and effect of the building parameters on energy consumption have been investigated. OTTV formula in MS1525 and Green Building Index (GBI) rating tool have been used for the OTTV calculation. The study shown that the OTTV of the Lot 4G11 is more than 70W/m2. In order to comply with MS1525, where the minimum OTTV shall be less than 50W/m2, improvement of the building envelope have been proposed, and the OTTV have been reduced below 50W/m 2 . Since the Government has set that all government buildings in Putrajaya shall be GBI certified, further improvement of building envelope have been made in order to achieve OTTV for Platinum certification. It is found that improving the Window to Wall Ratio (WWR), Shading Coefficient (SC) and U-value for glazing will further reduce the OTTV and improve the energy efficiency of the Lot 4G11. Detailed calculations have been conducted to compare the results in between Building Baseline, MS1525 and Platinum Design.